2001
DOI: 10.1242/dev.128.20.3975
|View full text |Cite
|
Sign up to set email alerts
|

Severe nasal clefting and abnormal embryonic apoptosis in Alx3/Alx4 double mutant mice

Abstract: A group of mouse aristaless-related genes has been implicated in functions in the development of the craniofacial skeleton. We have generated an Alx3 mutant allele in which the lacZ coding sequence is inserted in-frame in the Alx3 gene and the sequences encoding the conserved protein domains are deleted. Mice homozygous for this null allele are indistinguishable from wild-type mice. Compound mutants of Alx3 and Alx4, however, show severe craniofacial abnormalities that are absent in Alx4 single mutants. Alx3/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…Notably, mutations of some TF genes of Md-set have not yet been associated with jawbone disorders in humans. These synopses appear to contradict not only the RNA-seq, qPCR, and IF data for OB and raw jaw/tibia bones reported here but also the described mouse jawbone phenotypes for various mutations, such as Alx3 and Alx4 (Beverdam et al 2001), Dlx4 (Wu et al 2015), Msx1 (Nassif et al 2014), and Msx2 (Aïoub et al 2007). These observations support that jawbone abnormalities might also be present but not diagnosed in human disorders and highlight the need for systematic exploration of the jawbones while investigating skeletal and dental diseases.…”
Section: Discussioncontrasting
confidence: 87%
“…Notably, mutations of some TF genes of Md-set have not yet been associated with jawbone disorders in humans. These synopses appear to contradict not only the RNA-seq, qPCR, and IF data for OB and raw jaw/tibia bones reported here but also the described mouse jawbone phenotypes for various mutations, such as Alx3 and Alx4 (Beverdam et al 2001), Dlx4 (Wu et al 2015), Msx1 (Nassif et al 2014), and Msx2 (Aïoub et al 2007). These observations support that jawbone abnormalities might also be present but not diagnosed in human disorders and highlight the need for systematic exploration of the jawbones while investigating skeletal and dental diseases.…”
Section: Discussioncontrasting
confidence: 87%
“…In mouse and zebrafish, Alx1, Alx3, and Alx4 have been shown to be expressed in spatiotemporally restricted regions of the craniofacial mesenchyme (Zhao et al , ; Qu et al , ; ten Berge et al , ; Beverdam & Meijlink, ; Dee et al , ; Lours‐Calet et al , ). Evidence of gene compensation has previously been reported in animal studies (Beverdam et al , ; Dee et al , ). In studies of sea urchins, Alx4 was shown to be directly regulated by Alx1 (Rafiq et al , ; Khor et al , ).…”
Section: Discussionmentioning
confidence: 68%
“…Species-specific differences in alx1 gene functions may also reflect divergence in genetic compensation strategies employed by these organisms. In mouse, alx4 compensates for loss of alx3 since alx3;alx4 double mutants develop with severe orofacial clefts and single mutants do not ( Beverdam et al, 2001 ; Lakhwani et al, 2010 ). In zebrafish, single alx4a and alx4b mutants develop normally, while alx3 mutants exhibit medial ANC defects ( Mitchell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, ALX1 mutations are linked to severe frontonasal dysplasia (FND) and extreme microphthalmia, and ALX3 and ALX4 genes are associated with a phenotypic spectrum of hypertelorism and nasal-tip duplications ( Pini et al, 2020 ; Uz et al, 2010 ). These functions of alx genes are conserved in other vertebrates, but the pathogenic developmental mechanisms leading to the observed craniofacial malformations remain largely unknown ( Beverdam et al, 2001 ; Dee et al, 2013 ; Forsthoefel, 1963 ; Lakhwani et al, 2010 ; Lyons et al, 2016 ; Pini et al, 2020 ; Qu et al, 1999 ; Zhao et al, 1996 ). In mice, disruption of alx1 results in anencephaly, precluding analysis of its role in facial and ocular morphogenesis, while compound mutants of alx3 and alx4 present with FND-like defects ( Beverdam et al, 2001 ; Lakhwani et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%